2014
DOI: 10.5858/arpa.2014-0219-sa
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Role of the Pathologist in Determining Eligibility for Active Surveillance as a Management Option in Patients With Prostate Cancer: Consensus Statement With Recommendations Supported by the College of American Pathologists, International Society of Urological Pathology, Association of Directors of Anatomic and Surgical Pathology, the New Zealand Society of Pathologists, and the Prostate Cancer Foundation

Abstract: Active surveillance is an important management option for men with low-risk prostate cancer. Vital to this process is the critical role pathologic parameters have in identifying appropriate candidates for active surveillance. These findings need to be reproducible and consistently reported by surgical pathologists with accurate pathology reporting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(89 citation statements)
references
References 173 publications
2
85
0
2
Order By: Relevance
“…Due to known interobserver variability associated with the identification of minor Gleason pattern 4 elements, prospective intradepartmental consultation with colleagues should be considered a cornerstone of quality assurance in this area. 26,27 Pathologists should use uniform methodology when assessing and reporting the extent of cancer involvement in biopsy cores, especially when dealing with discontinuously involved cores 26 since volume and distribution of disease in prostate biopsies are also selection criteria for AS.…”
Section: Recommendationmentioning
confidence: 99%
“…Due to known interobserver variability associated with the identification of minor Gleason pattern 4 elements, prospective intradepartmental consultation with colleagues should be considered a cornerstone of quality assurance in this area. 26,27 Pathologists should use uniform methodology when assessing and reporting the extent of cancer involvement in biopsy cores, especially when dealing with discontinuously involved cores 26 since volume and distribution of disease in prostate biopsies are also selection criteria for AS.…”
Section: Recommendationmentioning
confidence: 99%
“…In addition to practical considerations, the use of biopsy is limited by sampling error and a dependence on subjective grading. 86 Conversely, Long et al 86 have demonstrated consistent gene expression across multiple biopsy cores in a single patient, supporting previous work revealing limited variation in gene expression levels of highly expressed genes across multiple biopsy cores, including both malignant and benign stromal tissue. 88 As others have noted, such consistent gene expression, despite tissue and tumor heterogeneity, supports the notion that one can be confident in the overall prostate biology based on analysis of a limited sample.…”
Section: Molecular Testing In Active Surveillancementioning
confidence: 56%
“…Ductal cancer's occasional central (non-peripheral zone) location may also result in undersampling. 6,16 In our study, 1/18 tumours were located exclusively in the transition zone, which was undersampled or not sampled at all during routine template TRUS-guided biopsies.…”
Section: Discussionmentioning
confidence: 74%
“…3,4 Ductal cancer detected on transrectal ultrasound (TRUS)-guided biopsy specimens warrants therapy and is considered a contraindication for active surveillance (AS). 5,6 The clinical and microscopic detection of ductal cancer can be challenging. Ductal adenocarcinoma secretes less prostatic serum antigen (PSA) than acinar adenocarcinoma and it can appear occult on some magnetic resonance imaging (MRI) sequences.…”
Section: Introductionmentioning
confidence: 99%